1986
DOI: 10.1177/0148607186010005494
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Growth Patterns in a Total Parenteral Nutrition Formulation Containing Lipid Emulsion

Abstract: Microbial growth of Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Candida albicans was evaluated in a standard amino acid-dextrose-based total parenteral nutrition (TPN) solution, 10% lipid emulsion, and a combined TPN formulation containing amino acids, dextrose, and lipid emulsion. At an initial inoculum of 10(4) CFU/ml, all three bacterial organisms grew well in 10% lipid emulsion, died in the standard solution and grew only minimally or died in the combined formulation. C. albicans gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 17 publications
1
27
1
2
Order By: Relevance
“…Previous in vitro studies with LCT showed that Candida grows better in a lipid-rich environment (5,11,24,36). We did not find a growth-enhancing effect on Candida for parenteral LCT, suggesting that with its metabolic breakdown, the effects of LCT on candidal growth disappear, in contrast with what occurs with MCT.…”
contrasting
confidence: 79%
“…Previous in vitro studies with LCT showed that Candida grows better in a lipid-rich environment (5,11,24,36). We did not find a growth-enhancing effect on Candida for parenteral LCT, suggesting that with its metabolic breakdown, the effects of LCT on candidal growth disappear, in contrast with what occurs with MCT.…”
contrasting
confidence: 79%
“…Category IA 2. Replace tubing used to administer blood, blood products, or lipid emulsions (those combined with amino acids and glucose in a 3-in-1 admixture or infused separately) within 24 hours of initiating the infusion [158,[226][227][228][229]. Category IB.…”
Section: Category Ib II Surveillancementioning
confidence: 99%
“…grow well in protein hydrolysate solutions but much less vigorously in the synthetic amino acid mixtures used for hyperalimentation today (61); bacterial growth generally is suppressed in synthetic amino acid solutions. Lipid emulsion supports the rapid growth of a wide variety of bacterial and fungal pathogens, including Candida (35, 55,126) and Malassezia spp., especially Malassezia furfur (6,100,155).…”
Section: Sources Of Microorganisms Causing Infusion-related Infectionsmentioning
confidence: 99%